Excellent Hybrid Polyurethane-Graphite Filler Micro Powder as a Lightweight Structure - Nugroho, Alvin Dio; Alandro, Daffa; Herianto, Herianto; Jamasri, Jamasri; Thirumalai, Sundararajan; Nugraha, Ariyana Dwiputra; Kusumawanto, Arif; Prawara, Budi; Muflikhun, Muhammad Akhsin (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Weight plays a significant role in the automotive and aerospace fields due to the demand of lightweight material structures. A lighter body in weight (BIW) and in structure can reduce fuel consumption, lessen emissions, and support the SDGs 9, 11, 12, and 13. Therefore, polyurethane (PU) foam is suitable for applications that require low weight. The characteristics of hybrid polyurethane-graphite micro were successfully evaluated in this study. Several tests have been used to characterize these structures, such as, compression, hardness, density, surface evaluation, and FTIR analysis. The results showed that the expansion and shrinkage variations lead to different shapes at specific ratios. Compression tests show that the highest value occurred at 0.84 kN, with a 4:1 ratio found in pure PU foam without any reinforcement. PU foam with 2% graphite filler showed the highest results at the 4:1 ratio with a value of 0.45 kN. Furthermore, the highest hardness test result was 37.7 SHD. Density testing indicates that the highest value is obtained from specimens with a 4:1 ratio of 0.077 g/cm3. FTIR testing reveals that adding graphite as a filler alters the chemical bonds during the formation of solid PU foam. Surface observations show that adding graphite as a filler influences the variation in material structure formation. All the evaluation has tended to conclude the present combination as suitable for lightweight structures applications.